Concerns about the safety of anti-TNF agents when treating rheumatic diseases. Issue 6 (2nd June 2020) - Atzeni, Fabiola; Nucera, Valeria; Gerratana, Elisabetta; Cirillo, Mariateresa; Marino, Francesca; Miceli, Gianfranco; Sangari, Donatella; Boccassini, Laura; Masala, Ignazio Francesco
ABSTRACT: Introduction: More than 15 years after its introduction, there is still no agreement as to whether anti-TNF treatment increases the risk of developing infections, cardiovascular or neurological diseases, or auto-antibodies. Anti-TNF drugs reduce inflammation and sub-clinical atherosclerosis in rheumatoid arthritis (RA) patients, but they also alter their lipid profiles and can lead to the development of severe infections. Furthermore, as they increase the risk of developing demyelinating diseases, are not recommended in patients with multiple sclerosis or related disorders. The authors searched the Medline database for English language articles concerning the adverse events of anti-TNF drugs published between 1998 and December 2019, and have summarized their contents relating to infections, malignancies, cardiovascular diseases, autoimmunity and neurological diseases. Patients should be fully informed of the increased risks associated with anti-TNF drugs, and physicians should know how to treat them. Areas covered: This review considers these safety concerns, their possible underlying causes, and other aspects that are important in clinical practice. Expert opinion: Growing concern about the safety of anti-TNF drugs underlines the need to ensure that all clinicians are capable of taking appropriate preventive and therapeutic action.